Salinity Affects Topsoil Organic Carbon Concentrations Through Regulating Vegetation Structure and Productivity. Issue 1 (15th January 2020) - Xue, Lian; Jiang, Junyan; Li, Xiuzhen; Yan, Zhongzheng; Zhang, Qian; Ge, Zhenming; Tian, Bo; Craft, Christopher
Abstract: Estuarine salt marshes have been recognized as one of the most efficient carbon sinks in the biosphere, with considerable potential for climate change mitigation. However, there are still uncertainties about the response of soil carbon stocks to enhanced soil salinization caused by accelerated sea‐level rises and aggravated saltwater intrusion. We therefore conducted both field investigations in the Chongming Dongtan salt marsh of the Yangtze River Estuary, China, and manipulative experiments on marsh soils occupied, respectively, by the invasive Spartina alterniflora, and the native Phragmites australis and Scirpus mariqueter, to identify the effects of elevated soil salinity on top soil organic carbon (SOC) concentration. Our field data showed that SOC concentrations were significantly positively associated with soil salinity concentrations, annual net primary productivity, and marsh surface elevation but showed a significant negative relationship with median grain size. Compared with the two native species, S. alterniflora preferred more saline conditions and had a higher SOC concentration. Although raised flooding salinities (0–35 ppt) did not strongly affect SOC concentrations, elevated soil salinities significantly corresponded with low SOC concentrations and plant biomass in manipulative experiments. These findings indicated that soil salinity, plant species, and soil texture were key factors controlling SOC concentrations in the studied salt marsh. Moreover, soil salinity could affect SOC concentrations through regulating vegetation spatial structure and plant biomass production. The further invasion of the S. alterniflora community will exert a positive influence on SOC concentrations in the Chongming Dongtan salt marsh. Plain Language Summary: Estuarine salt marshes are sedimentary environments that are among the most productive ecosystems on Earth and can continuously sequester carbon through plant production and sedimentary processes. Although sea‐level rises and saltwater intrusion may cause widespread soil salinization in estuarine ecosystems, its impact on top soil organic carbon (SOC) concentrations is highly uncertain. We therefore conducted field investigations that revealed the variation in SOC concentrations along a natural salinity gradient and manipulative experiments that raised flooding salinities from freshwater (0 ppt) to seawater (35 ppt) to identify the independent impacts of soil salinity on SOC concentrations. Our findings indicated that soil salinity was an important factor controlling SOC concentrations through indirectly regulating vegetation spatial structure and plant biomass production. Key Points: Soil salinity, plant species, and soil texture are key factors controlling topsoil organic carbon concentrations Soil salinity can affect topsoil organic carbon concentrations through regulating vegetation spatial structure and plant biomass production Further invasion of Spartina alterniflora will positively affect topsoil organic carbon concentrations in the Chongming Dongtan salt marsh